Select the simplified expression for 6(x - 6) - 2(x - 3) + 3x.

Question

Asked 11/17/2014 12:32:36 PM

Updated 11/17/2014 3:27:02 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/17/2014 3:27:02 PM]

s

= 4x - 16 - 2x + 6 + 3x

= 5x - 10

Question

Asked 11/17/2014 12:32:36 PM

Updated 11/17/2014 3:27:02 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/17/2014 3:27:02 PM]

Rating

8

6(x - 6) - 2(x - 3) + 3x

= 6x - 36 - 2x + 6 + 3x

= 4x - 30 + 3x

= 7x - 30

= 6x - 36 - 2x + 6 + 3x

= 4x - 30 + 3x

= 7x - 30

Added 11/17/2014 3:27:01 PM

This answer has been confirmed as correct and helpful.

2,349,000,000 Put This In Scientific Notation
**Weegy:** 2,349,000,000 in scientific notation is 2.349 x 10^9. (More)

Question

Expert Answered

Updated 11/16/2014 11:23:52 AM

0 Answers/Comments

How would you write this in scientific notation 0.0000000234 **Weegy:** 0.0000000234 written in scientific notation is 2.34 x 10^-8 (More)

Question

Expert Answered

Updated 11/16/2014 11:23:35 AM

0 Answers/Comments

Identify the solution(s) of the system of equations, if any.
-4x - 2y = 12
6y = -12x - 36 **Weegy:** -4X-2y=12
-12X-6Y=36
X=(12+2Y)/-4
substitute x to second equation
-12[(12+2Y)/-4]-6Y=36
36+6Y-6Y=36
0=0 **User:** Identify the solution(s) of the system of equations, if any.
x + 5y = 4
2x - 5y = 2 (More)

Question

Expert Answered

Updated 11/22/2014 2:35:17 AM

2 Answers/Comments

The solution(s) of the system of equations : -4x - 2y = 12 6y = -12x - 36 is it has infinite solutions .

-4x - 2y = 12 is equal to -2x - y = 6 ,

6y = -12x - 36 is also equal to -2x - y = 6 ,

so it has infinite solutions .

-4x - 2y = 12 is equal to -2x - y = 6 ,

6y = -12x - 36 is also equal to -2x - y = 6 ,

so it has infinite solutions .

Added 11/21/2014 7:10:55 PM

This answer has been confirmed as correct and helpful.

Deleted by andrewpallarca [11/22/2014 2:49:42 AM], Undeleted by andrewpallarca [11/22/2014 2:49:44 AM], Confirmed by andrewpallarca [11/22/2014 2:49:48 AM], Rated good by andrewpallarca

The solution(s) of the system of equations of x + 5y = 4 2x - 5y = 2 is x = 2 , y = 2/5.

equation 1 add equation 2 ,

x + 5y + 2x - 5y = 4 + 2

3x = 6

x = 2

2 + 5y = 4

5y = 2

y = 2/5 .

equation 1 add equation 2 ,

x + 5y + 2x - 5y = 4 + 2

3x = 6

x = 2

2 + 5y = 4

5y = 2

y = 2/5 .

Added 11/22/2014 2:35:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/22/2014 2:50:43 AM], Rated good by andrewpallarca

Identify the solution(s) of the system of equations, if any.
x + 5y = 4
2x - 5y = 2 **Weegy:** There are 3 terms here, in this expression x - 5y + 3 + x **User:** Identify the solution(s) of the system of equations, if any.
x + 5y = 4
2x - 5y = 2 **Weegy:** I can't graph it for you, [ but I can give you the information to plot.
Moving x over yields:
5y = 2x + 10
Dividing both sides by five will isolate y:
y = 2/5x + 2
This means that the line has a y-intercept of 2 (it crosses the y axis at 2) and a slope of 2/5 (or moves 5 x units for every 2 y units). ] **User:** Identify the solution(s) of the system of equations, if any.
4x + 2y = 4
y = 3 - 3x **Weegy:** 4x - 4y = 10 divided by 2 on both sides the result is: 2x - 2y = 5 (equ. 1) 3x + 2y = 5 (equ. 2) adding up equations 1 and 2 the result is: 5x = 10 x = 10/5 = 2 4(2) - 4y = 10 -4y = 10 - 8 = 2 y = 2/-4 = -1/2 The solution for the system 4x - 4y = 10 3x + 2y = 5 is (2, -1/2) (More)

Question

Updated 11/21/2014 5:48:38 PM

2 Answers/Comments

The solution(s) of the system of equations, x + 5y = 4 2x - 5y = 2 is x = 2, y = 2/5 .

Equation 1 add equation 2 ,

x + 5y + 2x - 5y = 4 + 2

3x = 6

x = 6/3

x = 2

put x = 2 in equation 1

2 + 5y = 4

5y = 2

y = 2/5 .

Equation 1 add equation 2 ,

x + 5y + 2x - 5y = 4 + 2

3x = 6

x = 6/3

x = 2

put x = 2 in equation 1

2 + 5y = 4

5y = 2

y = 2/5 .

Added 11/21/2014 5:45:40 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/21/2014 5:57:37 PM], Rated good by andrewpallarca

The solution(s) of the system of equations, 4x + 2y = 4 y = 3 - 3x is x = 1 , y = 0 .

Put equation 2 in equation

4x + 2(3 - 3x) = 4

4x + 6 - 6x = 4

-2x = -2

x = 1

y = 3 - 3*1

y = 0 .

Put equation 2 in equation

4x + 2(3 - 3x) = 4

4x + 6 - 6x = 4

-2x = -2

x = 1

y = 3 - 3*1

y = 0 .

Added 11/21/2014 5:48:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/21/2014 5:58:34 PM], Rated good by andrewpallarca

Determine the value of 3(x+6)-7 when x=7 **Weegy:** The value is 32. Solution:
3(x + 6)- 7 when x = 7;
3(7 + 6) - 7
= 3(13) - 7
= 39 - 7
= 32
(More)

Question

Expert Answered

Updated 11/17/2014 3:29:04 PM

1 Answer/Comment

Please provide solutions and calculations for math questions.

I edited your answer to input a solution.

Please read and follow the rules.

I edited your answer to input a solution.

Please read and follow the rules.

Added 11/17/2014 3:29:04 PM

34,467,066

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 818 [Total 6691] Ratings 19 Comments 628 Invitations 0 Offline

There are no comments.